ANALISIS STRUKTURAL NASKAH DRAMA CINDUAMATO KARYA WISRAN HADI - Mardalena, Siska - (Pendidikan Bahasa Indonesia, 2014)
This research is motivated by the following points: First , in Cindua Mato plays Wisran Hadi works contained elements of character , and character roles . Second , there is an element motifs that causes an event and conflict . Third , the cultivation of the language used is easy to understand and straightforward . Fourth , in Cindua Mato plays Wisran Hadi works are the theme of the struggle in defense of truth . Fifth , many mandate that can be learned in a play Cindua Mato Wisran Hadi works . This study aimed to describe the elements of character, role, character, motives, events, conflict, plot, setting, space, the cultivation of language, theme, and the mandate contained in the works of playwright Cindua Mato Wisran Hadi.This research is a descriptive qualitative research method. Based on the results, it can be concluded that plays Cindua Mato Wisran work this Hadi has thirteen figures. These figures have the role and character of each. The flow used was developed flow. Background contained in the works of playwright Cindua Mato Wisran Hadi consists of setting the place, time and social. The appropriation of the language in the plays Cindua Mato according to the style or styles Wisran Hadi. The text of the play has a theme that is Cindua Mato courage in defense of truth . Mandate that can be taken from a play by Cindua Mato Wisran Hadi works are: ( a) do not seize the property of others, ( b ) do not involve the people above personal interests. ( c ) do not be accusatory and suspicious of others. ( d ) do not hold a grudge against someone else .